Praktik Jual Beli Pakaian Bekas Ditinjau dari Hukum Positif dan Hukum Islam - Aprilia, Riska Putri; Soelistyo, Poernomo A; Ramadhan, Zaky (Journal of Fiqh in Contemporary Financial Transactions, 2024)
The purpose of this research is (1) To understand the practice of buying and selling second-hand clothing. (2) To understand the practice of buying and selling second-hand clothing from the perspective of positive law. (3) To understand the practice of buying and selling second-hand clothing from the perspective of Islamic law along with the practice of khiyar aib within it. This research is an empirical study using a qualitative descriptive approach. The results of the research indicate that: In the context of positive law in Indonesia, the prohibition of importing second-hand clothing is regulated by Minister of Trade Regulation No. 40 of 2022, a revision of No. 18 of 2021. Despite the prohibition, the sale of second-hand clothing continues to be popular because it provides greater profit and meets the needs of consumers who want unique products. Positive law provides the legal basis with administrative and criminal sanctions according to Law Number 7 of 2014. In the context of Islamic law, the practice of buying and selling second-hand clothing in Depok City is considered valid because it fulfills the pillars and conditions of buying and selling, where people have the freedom to choose clothes before the transaction.